A review of the mechanical properties and durability of basalt fiber-reinforced concrete. (12th December 2022) - Zheng, Yuanxun; Zhang, Yu; Zhuo, Jingbo; Zhang, Yamin; Wan, Cong
Highlights: 137 papers are reviewed on basalt fiber-reinforced concrete (BFRC). Influences of basalt fiber (BF) on the mechanical properties and fracture properties of BFRC are reviewed. Effects of BF on the durability and the microstructure of BFRC are discussed. Further suggestions for the research and application of BFRC are proposed. Abstract: In recent years, basalt fiber (BF) has been extensively used as a reinforced fiber to improve the mechanical properties and durability of concrete because of its excellent mechanical properties, high-temperature resistance, acid and alkali resistance, availability of raw materials, and environmentally friendly production processes. Based on a thorough review of recent literature, the current research status of basalt fiber-reinforced concrete (BFRC) in terms of the basic mechanical characteristics, fracture performance, and durability under different test conditions were reviewed in this study, and future research directions and trends were predicted and analyzed. It is shown that the reasonable addition of BF with a diameter of approximately 10–20 μm, length of approximately 12–20 mm, and an optimal volume fraction of approximately 1 % in concrete can better improve the mechanical properties of concrete. Furthermore, BF significantly improves the fracture toughness, fracture energy, and maximum deflection of concrete, effectively increasing the impermeability, resistance to concrete chloride erosion, and sulfate attack. In addition, the advancements in methods for the numerical simulation of concrete fractures and calculation of the chloride ion permeability coefficient were also summarized in this paper. Based on the shortcomings of the current study, it is suggested that future studies should focus on the mechanical properties and durability of BFRC under high-temperature and after damage. The toughening mechanism of BF on hydraulic concrete concrete should be studied, with the objective of laying the theoretical foundation for its application in practical engineering.